Prevalence and factors associated with hypertension in rural areas of Naubatpur block of Patna District in Bihar, India: a population−based cluster cross−sectional study - Ranjan, Alok; Pandey, Sanjay; Kumar Nirala, Santosh; Singh, Chandramani; Bhardwaj, Mohit (BMC public health, 2025)
Background Hypertension is a serious public health challenge with varying incidence at the global and national levels. The prevalence of hypertension has been rising in low− and middle−income countries (LMICs) like India. Hypertension, previously considered an urban issue, is increasingly prevalent in rural India, necessitating targeted interventions. Objective To estimate the prevalence of hypertension, and the various associated factors among the rural population of Naubatpur block of Patna district in Bihar state. Methodology A population−based, cluster cross−sectional study was conducted among 840 adults, selected randomly using a two−stage cluster sampling method. Data on socio-demographics and economic, anthropometric, family history, lifestyle variables, and awareness were collected using a pre−tested standardized structured questionnaire. Standard WHO procedures were used to measure blood pressure and anthropometric variables. Stata version 17 was used for statistical analyses considering cluster survey data using sampling weights. Bivariate analysis was performed to estimate crude odds ratios (ORs) with 95% confidence intervals. A multivariate logistic regression model was used, taking variables with p −value ≤ 0.20 in bivariate analysis as independent variables and hypertension as dependent variables to estimate adjusted ORs with 95% confidence intervals. Results The weighted prevalence of hypertension in adults was 24.55% (95% CI: 20.66 – 28.9%) higher than the National Family Health Survey (NFHS-5) data of Bihar. Nearly 25.35% of subjects were classified in the pre−hypertension stage according to JNC VII criteria. Based on three regression models, the odds of having hypertension increased significantly with an increasing trend as age advanced, family history of hypertension, tobacco chewing, Obesity (BMI > 25.5), and salt consumption (> 5gm/day) were found to be significantly associated with the prevalence of hypertension among adult population of rural areas after controlling for all the confounders. Conclusions The high prevalence of hypertension and pre−hypertension among the adult population residing in the rural area is a serious public health concern. Public health policymakers and professionals need to create awareness, early identification, and prevention programs in rural areas to focus on modifiable behaviors in rural areas to combat the menace of diseases associated with hypertension.